Minimization of nitrogen-based contaminants in surface water using treated clay particles for phytoremediation enhancement - Mohd Zaini, Nurul Solehah (2020)
Nitrogen contamination has become the main element of surface water pollution, leading to eutrophication and water quality deterioration that affect the aquatic ecosystem. The source of contaminant is majorly coming from the run-off fertilizer of the nearby agricultural activities. The long retention time of N contamination affects the surface water's ecosystem and green technology approaches such as phytoremediation come as a solution to water contamination issues. However, the phytoremediation process alone was less efficient in reducing the N contamination such as ammonium, NH4+ and nitrate, NO3- accumulation in the system and has caused the compound to accumulate in bulk instead of to be absorbed by the plant. Recent workers seek to improve the phytoremediation process as a safer treatment alternative to replace the commercial method that used physical and chemical treatment. Adsorption of the contaminants using clay particles serves as a green approach technique in polishing and improving the phytoremediation process. Therefore, the objectives of this study were to characterize the treated clay by adjusting the pH to acidic and basic condition followed by the spray dry method. Then, to analyze the adsorption capacity of the pH-treated clay particles of two different clay components; bentonite and kaolin, and to evaluate the enhanced phytoremediation process's water treatment performance using treated clays and macrophytes plant (Nelumbo nucifera). In this study, the clay particles were spray-dried after treated with varying pH conditions ranging from pH 2 to pH 10. The pH-treated clays were characterized by using Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), and X-Ray Fluorescence (XRF). The treated clay particles were subjected to the ammonium solution, and their adsorptive capacity was measured in terms of the ammonium removal efficiency, adsorption isotherm, and zeta potential value. The treated clay particles were subjected to the phytoremediation system, and the water treatment performance was evaluated. Nitrate was measured due to the conversion of ammonium to nitrate by microbes in the phytoremediation system. From the obtained results, the characterization results for SEM illustrated that bentonite’s surface has more folded, richly wrinkled, and more pore compare to the less wrinkled and flat surface morphology of kaolin. XRF explained the presence of Fe and Ca element proving high isomorphous substitution in bentonite compare to kaolin. XRD showed the presence of montmorillonite mineral in bentonite that helps in the swelling capacity of bentonite. For the adsorption capacity, bentonite showed higher adsorption than kaolin with the maximum adsorption (qmax) of 7.463 mg/g and fitted well with the Langmuir model isotherm. Application of pH-treated clay particles obtained from the local soil sources with the Nelumbo nucifera plant successfully polished the water quality of the contaminated surface water by increasing the removal efficiency of NO3-> ninety-eight percent compared with the neutral pH-treated and control. The finding is expected to enhance the current phytoremediation practiced and help the local authorities to improve the quality of the contaminated surface water on a larger scale in the future.